Syndemic Framework Evaluation of Severe COVID-19 Outcomes in the United States: Factors Associated With Race and Ethnicity - Williams, Christopher; Vermund, Sten H. (Frontiers in Public Health, 2021)
Socially and economically disadvantaged racial and ethnic minorities have experienced comparatively severe clinical outcomes from the coronavirus disease (COVID-19) pandemic in the United States. Disparities in health outcomes arise from a myriad of synergistic biomedical and societal factors. Syndemic theory provides a useful framework for examining COVID-19 and other diseases that disproportionately affect vulnerable populations. Syndemic models ground research inquiries beyond individual clinical data to include non-biological community-based drivers of SARS-CoV-2 infection risk and severity of disease. Given the importance of such economic, environmental, and sociopolitical drivers in COVID-19, our aim in this Perspective is to examine entrenched racial and ethnic health inequalities and the magnitude of associated disease burdens, economic disenfranchisement, healthcare barriers, and hostile sociopolitical contexts—all salient syndemic factors brought into focus by the pandemic. Systemic racism persists within long-term care, health financing, and clinical care environments. We present proximal and distal public policy strategies that may mitigate the impact of this and future pandemics.